2017
DOI: 10.1002/2016ja023475
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN NGIMS observations of atmospheric gravity waves in the Martian thermosphere

Abstract: Gravity waves have a significant impact on both the dynamics and energy budget of the Martian thermosphere. Strong density variations of spatial scales indicative of gravity waves have previously been identified in this region by using in situ observations. Here we use observations from the Neutral Gas and Ion Mass Spectrometer (NGIMS) mass spectrometer on Mars Atmosphere and Volatile EvolutioN Mission to identify such waves in the observations of different atmospheric species. The wave signatures seen in CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 55 publications
13
130
1
1
Order By: Relevance
“…Both observations and GCM simulations support that the dust storms have vital impacts on the Mars atmosphere up to the upper layers (e.g., England et al, ; Keating et al, ; Montabone et al, ; Rafkin et al, ), which means the dust terms in equation (6) are reasonable. The general impact of the dust storms on the Mars atmosphere is to expand and lift the atmospheric layers (Smith, ).…”
Section: Results and Analysismentioning
confidence: 86%
“…Both observations and GCM simulations support that the dust storms have vital impacts on the Mars atmosphere up to the upper layers (e.g., England et al, ; Keating et al, ; Montabone et al, ; Rafkin et al, ), which means the dust terms in equation (6) are reasonable. The general impact of the dust storms on the Mars atmosphere is to expand and lift the atmospheric layers (Smith, ).…”
Section: Results and Analysismentioning
confidence: 86%
“…For the atmospheric altitudes examined in the present work (~160–200 km), the lower altitude region (below 180 km) has ion‐neutral collision timescales of seconds (Matta, ), whereas the gravity wave timescales are on the order of minutes (e.g., Walterscheid et al, ). At higher altitudes (above 180 km), the timescales for collisions and gravity wave propagation become comparable, but the length scales of gravity wave perturbations (tens to hundreds of km) are expected to dissipate near ~200 km (England et al, ), whereas the observed plasma‐specific perturbations are observed to occur over much smaller (few kilometers) length scales, as shown in Figure B. The effects of atmospheric waves on the upper Martian ionosphere cannot be ruled out at this time, but length and timescale comparisons necessitate more careful investigation and simulation for quantitative assessments.…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the challenges to identify such signature in MAVEN data is to distinguish an exospheric profile induced by dissociative recombination and sputtering from one induced by thermospheric waves (England et al, 2017). Both induced exospheric densities and atmospheric escape are negligible when compared to the equivalent contributions caused by the dissociative recombination of the main ion, O 2 + , in Mars's ionosphere.…”
Section: Resultsmentioning
confidence: 99%